Pengaruh Profitabilitas, Sales Growth, dan Operating Cash Flow terhadap Financial Distress (Studi Empiris pada Perusahaan Manufaktur Subsektor Food & beverage yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Halim, Michelle Juliana; Riswan (Jurnal EMT KITA, 2024)
This study aims to analyze the impact of profitability (X1), sales growth (X2), and operating cash flow (X3) on financial distress in food & beverage manufacturing companies listed on the Indonesia Stock Exchange during the period 2019 to 2021. The research adopts a quantitative approach. The total population consists of 810 companies listed on the IDX during the period 2019 to 2021. The sample comprises 18 companies selected through purposive sampling technique. Data analysis method employs logistic regression. The results demonstrate that profitability and sales growth have a negative effect, while operating cash flow has a positive effect on financial distress.